PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI SEKOLAH, DAN KOMPENSASI GURU TERHADAP KINERJA GURU DI SEKOLAH MENENGAH KEJURUAN PARAWISATA KOTA TANGERANG SELATAN - Desnimar; Lili Nurlaili; Surasni (STKIP Subang, 2026)
This study aims to analyze the influence of organizational culture of transformational leadership and teacher compensation partially or simultaneously on teacher performance at Tourism Vocational High School in South Tangerang City. The research approach used is quantitative with associative method. The population in this study were all teachers in South Tangerang City. with a sample of 135 respondents. Data collection techniques were carried out through questionnaires with Likert scale instruments that have been tested for validity and reliability. Data analysis includes classical assumption tests and multiple linear regression analysis using SPSS software version 27. The results of the study indicate that partially, there is a positive and significant influence of transformational leadership on teacher performance with the equation model Y = 1.399 + 0.917 X1. Organizational Culture is also proven to have a positive and significant influence on teacher performance with the model Y = 1.399 + 0.993 X2. Likewise, teacher compensation has a positive and significant influence on teacher performance through the equation model Y = 1.399 + 0.214 X3. Simultaneously, these variables contribute a very strong influence on teacher performance. As an illustration, the correlation test between organizational culture, infrastructure, and the work environment collectively showed a 90.0% contribution to teacher performance, while the remaining 10.0% was influenced by factors outside the research variables. This indicates that effective teacher performance improvement can be achieved through strengthening the highly influential organizational culture, providing adequate infrastructure, and continuously improving the work environment.